Human Placenta Expresses α(2)-Adrenergic Receptors and May Be Implicated in Pathogenesis of Preeclampsia and Fetal Growth Restriction - Motawea, Hanaa K.B. (Am J Pathol, 2018)
α(2)-Adrenergic receptors (α(2)ARs) are G-protein–coupled receptors involved in catecholamine signaling by extracellular regulated protein kinase 1 and 2 (ERK1/2) pathways. We examined placental expression and function of α(2)AR subtypes in women with severe preeclampsia (sPE) with and without intrauterine growth restriction (IUGR). Placental biopsies were analyzed from 52 women with i) sPE (n = 8); ii) sPE + IUGR (n = 9); iii) idiopathic IUGR (n = 8); iv) idiopathic preterm birth (n = 16); and v) healthy term controls (n = 11). Expression of α(2)AR subtypes (α(2A), α(2B), α(2C)) and phospho-ERK1/2 (receptor activation marker) was investigated by immunohistochemistry and/or quantitative real-time RT-PCR. The effects of α(2C)AR knockdown on syncytialization (syncytin-1 and -2) and β-human chorionic gonadotropin secretion were examined in BeWo cells stimulated with forskolin. The effects of α(2)AR agonist UK 14,304 and specific α(2C)AR antagonist were tested, using a trophoblast migration assay. All three α(2)ARs were expressed and functionally active in human placenta with site-specific localization. Highest α(2B)AR and α(2C)AR mRNA expression was identified in sPE + IUGR. α(2C)AR knockdown increased expression of syncytin-1 and -2 but decreased secretion of β-human chorionic gonadotropin. UK 14,304 impaired trophoblast migration. The observed α(2)AR expression pattern suggests different function for each subtype. α(2C)AR modulates trophoblast syncytialization and migration and may carry pathogenic role in sPE + IUGR.